Examine the Role of Psychological Resilience in Predicting Social and Professional Performance in Patients with Diabetes, Multiple Sclerosis, and Rheumatism - Ahmad S Alsheikh Al; Ashraf Alqudah (Health Psychology Research)
Psychological resilience is one of the most important factors that help a person adapt to the difficulties of life. The present study aimed to examine the role of psychological resilience in the social and professional functioning of patients with multiple sclerosis (MS), diabetes mellitus, and rheumatoid arthritis (RA). A total of 301 individuals (58.8% female) participated in the study. Approximately 44% of participants were diagnosed with diabetes, 28% with rheumatoid arthritis, and around 25% with multiple sclerosis. Two psychometric measures were used to achieve the objectives of the present study: the Psychological Resilience Scale and the Performance of Social and Occupational Functions Scale. Regression analyses were used to examine the amount of variance predicted by psychological resilience in terms of the following variables of social and professional functions: relationships, communication, social activities, entertainment activities, life skills, employment-based job functions, and unemployment-based job functions. Results revealed that psychological resilience positively predicted social and occupational functions among all illnesses. Resilience best predicted social and professional functions among MS patients, followed by diabetes patients and RA patients. These findings highlight the role of psychological resilience in improving the social and occupational performance of patients with chronic illnesses and the positive relationship between employment and resilience.